Sistem Informasi Apotek Berbasis Web Menggunakan Metode Personal Extreme Programming ( PXP ) Dengan Arsitektur MVC - cindy Lahama; Chriestie Ellyanne Juliet Clara Montolalu; Edwin Tenda (Indonesian Journal of Intelligence Data Science, 2024)
A web-based drug store data framework is outlined to encourage the productive administration and deals of solutions in a drug store with consistent integration. To realize this objective, the Individual Extraordinary Programming (PXP) strategy has been received to oversee the development of this framework. Within the setting of this venture, the PXP strategy is custom fitted to a littler advancement environment. The drug store data framework is outlined with the Model-View-Controller (MVC) engineering, which isolates commerce rationale, introduction, and client interaction into unmistakable components. This points to improve adaptability, versatility, and generally framework practicality. The results of this extend are anticipated to provide a web-based drug store data framework open through a user-friendly interface, proficient in pharmaceutical stock administration, and supporting exact installment frameworks. As a result, it is expected that operational proficiency and client benefit will altogether progress.